2017
DOI: 10.7232/iems.2017.16.1.064
|View full text |Cite
|
Sign up to set email alerts
|

Biological Feature Selection and Disease Gene Identification using New Stepwise Random Forests

Abstract: Identifying disease genes from human genome is a critical task in biomedical research. Important biological features to distinguish the disease genes from the non-disease genes have been mainly selected based on traditional feature selection approaches. However, the traditional feature selection approaches unnecessarily consider many unimportant biological features. As a result, although some of the existing classification techniques have been applied to disease gene identification, the prediction performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The Gene Ontology resources provides a model of hierarchically (ancestors-descendants relationship) organized directed acyclic graph (DAG) having GO-terms as nodes and functional association as directed edges within each hierarchy by ‘ is_a ’ (subtype) and ‘ part_of ’ (component) relationship associated to gene/protein functionality (molecular function, cellular component and biological process) description 73,74 . GO based biological process (GO-BP) provides cohesive evidences about protein interactions related to both physical and functional networks of molecular events involved in cellular physiology 83–85 . The candidate genes for a disease show common biological pathway(s) 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The Gene Ontology resources provides a model of hierarchically (ancestors-descendants relationship) organized directed acyclic graph (DAG) having GO-terms as nodes and functional association as directed edges within each hierarchy by ‘ is_a ’ (subtype) and ‘ part_of ’ (component) relationship associated to gene/protein functionality (molecular function, cellular component and biological process) description 73,74 . GO based biological process (GO-BP) provides cohesive evidences about protein interactions related to both physical and functional networks of molecular events involved in cellular physiology 83–85 . The candidate genes for a disease show common biological pathway(s) 48 .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, The current studies have several limitations, which can be summarized in the following points. First, most studies have developed methods to predict the genes related to disease, but a few of these methods were designed for PD-genes prediction 13,14,[16][17][18] . Second, some of these PD methods identified only protein genes related to PD and ignored lncRNA genes, whether lncRNAs is critical for improving our understanding and diagnosing different diseases 12,20,22,23 .…”
Section: Related Workmentioning
confidence: 99%
“…Based on ensemble-weighted classifiers, they built the EPU learning to predict disease-related genes. Hwang 18 proposed stepwise random forests (SRF) method to select the biological features for identifying genes related to the disease. First, they integrated multiple biological features from the gene characteristics, such as protein domains, gene ontology, and human protein interactions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results have confirmed that the classifier built with high-dimensional features may not be an efficient in terms of detection of PD. Hwang [17] proposed a SRF (Stepwise Random Forests) approach for disease gene identification on biological data sources used by Yang. He had enhanced his method by considering only important features with filter-based feature selection method for classification.…”
Section: Related Workmentioning
confidence: 99%